A Novel Fragmentation Sensitivity Index Determines the Susceptibility of Red Blood Cells to Mechanical Trauma - Ugurel, Elif; Goksel, Evrim; Goktas, Polat; Cilek, Neslihan; Atar, Dila; Yalcin, Ozlem (Frontiers in Physiology, 2021)
Supra-physiological shear stresses (SS) induce irreversible impairments of red blood cell (RBC) deformability, overstretching of RBC membrane or fragmentation of RBCs causing free hemoglobin to be released into plasma, which may lead to anemia. The magnitude and exposure time of the SS are two critical parameters to determine the hemolytic threshold of a healthy RBC. However, impairments in the membrane stability of damaged cells reduce the hemolytic threshold and increase the susceptibility of the cell membrane to supra-physiological SS that leads to cell fragmentation. The severity of the RBC fragmentation as a response to mechanical damage and the critical SS levels causing fragmentation are not previously defined. In this study, we investigated RBC mechanical damage in oxidative stress (OS) and metabolic depletion (MD) models by applying supra-physiological SS up to 100 Pa by an ektacytometer (LORRCA MaxSis) and assessed RBC deformability. Next, we examined hemolysis and measured RBC volume and count by Multisizer 3 Coulter Counter to evaluate RBC fragmentation. RBC deformability was significantly impaired in the range of 20-50 Pa in OS compared to healthy controls (p<0.05). Hemolysis was detected at 90-100 Pa SS levels in MD and all applied SS levels in OS. Supra-physiological SS increased RBC volume in both damage models and control group. The number of fragmented cells increased at 100 Pa SS in the control and MD and at all SS levels in OS, which is accompanied by hemolysis. Fragmentation sensitivity index (FSI) increased at 50-100 Pa SS in the control, 100 Pa SS in MD and at all SS levels in OS. Therefore, we propose RBC fragmentation as a novel sensitivity index for damaged RBCs experiencing a mechanical trauma before they undergo fragmentation. Our approach for the assessment of mechanical risk sensitivity by RBC fragmentation could facilitate the close monitoring of shear-mediated RBC response and provide an effective and accurate method for detecting RBC damage in mechanical circulatory assist devices used in routine clinical procedures.